Trans-regulation of thoracic homeotic selector genes of the Antennapedia and bithorax complexes by the trithorax group genes: absent, small, and homeotic discs 1 and 2. - LaJeunesse, D.R.; Shearn, A. (Mechanisms of Development, 1995)
Genes of the trithorax group appear to be required for the maintenance of expression of the homeotic selector genes of the Antennapedia and bithorax complexes. According to genetic criteria, the Drosophila melanogaster genes absent, small, or homeotic discs 1 and 2 (ash1 and ash2) are members of the trithorax group. In this paper we examine the consequences of ash1 and ash2 mutations on the expression of homeotic selector genes in imaginal discs. The results of these experiments demonstrates that both ash1 and ash2 are trans-regulatory elements of homeotic selector gene regulation. Hypomorphic ash1 mutations cause variegated expression of Antennapedia, Sex combs reduced, Ultrabithorax, and engrailed. Complete loss of ash2 activity causes the loss of expression of Sex combs reduced in first leg imaginal discs, loss of expression of Ultrabithorax in third leg discs, and a late-patterned loss of expression of Ultrabithorax within haltere discs, yet has no effect on engrailed or Antennapedia expression. These results suggest that the range and action of trithorax group genes is varied and complex and argue against any model in which all of the products of the trithorax group act together in a single mechanism or complex.